Media and Political Discourse: The Nigerian experience - Bashir, Muktar; Abba Pali, Nazif (School of Social Sciences, USM, 2017)
and development of every society. It is a tool which can be used to re-orientate, influence and guide the masses particularly in this democratic dispensation of Nigeria. Therefore, modern political environment cannot be sustained anywhere in the world without the presence and vibrant role of the media. The media is expected to discharge it social responsibility in the political domain of Nigeria. It is in view of this, the paper explore the pivotal role of the media in the democratic politics of Nigeria, with a view to understanding its contribution in the political development of the country. Social responsibility theory has been adopted in this paper to serve as guide in explaining the issue under investigation. The paper adopts secondary sources in generating useful data for the study, they include; journals, periodicals, articles, books, internet materials and conference papers that have direct bearing on the subject matter. It is suggested that the media should be professional and live up to the expectation of the public by disseminating vital and truthful information in line with the constitutional provision of the country, which will raise the political consciousness of the citizens to effectively contribute in the development of the political environment.